Mājokļa piejamības atbalsta politika Latvijā 20.gadsimta otrajā pusē - Briķe, Ilze (Latvijas Universitāte, 2009)
The goal of the diploma work “Affordable housing policy in 20th century Latvia” is to study the aspects of housing policy in Soviet Socialist Republic of Latvia as well as in Republic of Latvia, starting from the middle of the 20th century up to year 2005, taking in to consideration the situation on the housing level at this moment, as well as to work out proposals to improve the document and normative base for the affordable housing policy. The author of the diploma work compares two different political system basic approaches towards Housing policy – availability of apartments in Soviet Socialist Republic of Latvia and availability in Republic of Latvia in 20th century. Housing (apartment) policy in Soviet Union (including Soviet Socialist Republic of Latvia) was defined as political, economical and social measures, generally directed to solve the housing questions as social problem. Solution of the housing question was one of the main social politics directions, according to which the wide apartment construction programs were realized. In Latvia by working out the housing policy has to be taken in to account the basic goals of housing policy of European Union, which includes not only the housing affordability questions, but also housing quality minimal standards and evaluation of its influence to environment. In Latvia have to be defined the following concepts “housing policy” and “adequate housing”.

АНОТАЦИЯ Цель дипломной работы „Политика поддержки жиличной политики во второй половине 20 века” - изучить аспекты жиличной политики как в Латвийской Советской Социалистической республики (Латвииская ССР), так и в Латвийской республике, начиная с середины 20 века до 2005 года, включая взгляды внынешней жилищной ситуаций, а также разработать предложения дальнеишей доступности жилищной политики в улучшении документов и нормативной базы. В дипломной работе автор сравнивает два политических устройства в постановке жилищной политике – доступ квартир в Латвийской ССР и доступ квартир в Латвийской республике в 20 веке. Жилищная (квартирная) политика в Советском Союз&#1077
Affordable housing policy in second part of 20th century Latvia
Keywords: Tiesības